Analytical Evaluation of Reinforced Concrete Pier and Cast-in-Steel-Shell Pile Connection Behavior considering Steel-Concrete Interface - Jiho Moon; Dawn E. Lehman; Charles W. Roeder; Hak-Eun Lee; Tae-Hyung Lee (Advances in Materials Science and Engineering)
The seismic design of bridges may require a large-diameter deep pile foundation such as a cast-in-steel-shell (CISS) pile where a reinforced concrete (RC) member is cast in a steel casing. In practice, the steel casing is not considered in the structural design and the pile is assumed to be an RC member. It is partially attributed to the difficulties in evaluation of composite action of a CISS pile. However, by considering benefits provided by composite action of the infilled concrete and the steel casing, both the cost and size of CISS pile can be reduced. In this study, the structural behavior of the RC pier and the CISS pile connection is simulated by using an advanced 3D finite element (FE) method, where the interface between the steel and concrete is also modeled. Firstly, the FE model is verified. Then, the parametric study is conducted. The analysis results suggest that the embedment length and the friction coefficient between the steel casing and the infilled concrete affect the structural behavior of the RC pier. Finally, the minimum embedment length with reference to the AASHTO design guideline is suggested considering the composite action of the CISS pile.